The Tomba dei Tori at Tarquinia: A ritual approach - Brandt, J. Rasmus (Nordlit, 2014)
In a recent publication (Brandt 2014b) an attempt was made to single out recurring pictorial motifs in Etruscan tomb paintings and to interpret them as elements of funerary ritual procedures with reference to Arnold van Gennep’s rites-de-passage model (1908) and Mary Douglas’ views on purity and danger (1996). The model is here applied on the Archaic and well-known Tomba dei Tori at Tarquinia in order to see if the tomb’s many enigmatic pictorial scenes can be read as coherent elements of such procedures.